Improving quality of life of completely edentulous patient with oral submucous fibrosis and infantile hemangioma - Shubhaani Singh; Pankaj Dhawan; Harsimran Kaur; Manish Bhargava (European Journal of Translational and Clinical Medicine, 2025)
Background: Oral submucous fibrosis is a premalignant condition characterized by rigidity of lips, tongue, and buccal mucosa. It makes rehabilitation difficult as it affects the stability and retention of the prosthesis. Description: This technical report focuses on the use of intralesional hyaluronidase injections followed by conventional complete denture fabrication for an edentulous patient. These conservative and non-invasive options were chosen due to the presence of infantile hemangioma in the region of interest. Conclusion: Hyaluronidase injections in the area of oral submucous fibrosis can bring about a major difference in the process of rehabilitation and potentially eliminate the morbidity associated with the surgical procedures.